Atheist secularism and its discontents: a comparative study of religion and communism in Eurasia - Ngo, Tam T. T.; Quijada, Justine B. (Global diversities, 2015)
Atheist Secularism and Its Discontents takes a comparative approach to understanding religion under communism, arguing that communism was integral to the global experience of secularism. Bringing together leading researchers whose work spans the Eurasian continent, it shows that appropriating religion was central to Communist political practices